OPTIMALISASI TERHADAP PENGAWASAN ALIRAN KEPERCAYAAN DAN ALIRAN KEAGAMAAN DALAM MENJAGA KETENTRAMAN DAN KETERTIBAN UMUM - Samiadji Noer (2020)
Supervision of religious beliefs and sects in society for public order and peace is carried out by the Attorney General's Office of the Republic of Indonesia, which is the scope of duties, powers and functions of the Attorney General's Office in the field of Judicial Intelligence (law Intelligence) which leads to Investigation activities. The problems of this research are 1). How is the optimization in the implementation of Supervision of Beliefs and Religious Sects in maintaining peace and public order? 2). What are the obstacles faced in optimizing the implementation of supervision of Beliefs and Religious Sects in maintaining public order and order? By using the juridical normative and empirical juridical research types, it is known that 1) optimization in the implementation of the Supervision of Beliefs and Religious Sects is done in a preventive manner such as outreach to the public. 2) the obstacles faced in the supervision of religious beliefs and religious sects, the factor of authority and society with minimal legal awareness, is influenced by factors or elements that influence it, namely, among others, legal factors, law enforcement factors, facilities or facilities factors, factors society and cultural factors.